Ethical Consumers Among the Millennials: A Cross-National Study - Bucic, Tania (Journal of business ethics, 2012)
Using two samples drawn from contrasting developed and developing countries, this investigation considers the powerful, unique Millennial consumer group and their engagement in ethical consumerism. Specifically, this study explores the levers that promote their ethical consumption and the potential impact of country of residence on cause-related purchase decisions. Three distinct subgroups of ethical consumers emerge among Millennials, providing insight into their concerns and behaviors. Instead of being conceptualized as a single niche market, Millennials should be treated as a collection of submarkets that differ in their levels of awareness of ethical issues, consider discrete motives when making consumption decisions, and are willing to engage in cause-related purchasing to varying degrees. These findings have several critical implications for theory and practice.